STUDY OF MUSLIM MONUMENTS OF STARY KRYM IN THE SECOND HALF OF THE 1920s: NEW MATERIALS - D. A. Lomakin (Вестник Кемеровского государственного университета, 2014)
Using new archive materials, that are introduced into scientific use for the first time, the paper recreates the final stage of the State Palace Museum of Turkish and Tatar Culture in Bakhchisaray’s study of Muslim monuments of the Golden Horde period in Stary Krym. The reasons for termination of the research of archaeological monuments in the city are analyzed.